The Expression of Dual in Old Armenian According to Antoine Meillet - GEVORGYAN, ARMINE (Bulletin of Yerevan University B: Philology, 2021)
Dual number has not been a peculiar feature of literary Armenian in any stage of its development, however, some researchers, including Antoine Meillet, mark separate forms of dual number in Classical Armenian (cf. աչք, ականջք, ծունգք). It is quite natural, if we take into account the fact that Armenian is an Indo-European language, and most of Indo-European old languages (Old Indian, Ancient Greek, Latin, Pre-Slavic languages) had maintained the form of the dual number as a grammatical category inherited from the Proto-Indo-European language. Scholars dealing with Armenological studies differentiate forms of dual number containing the particles ուի/ւի/վի in some Modern Armenian dialects (dialects of Hemshin, Van, Svedia, Zeytun), and it is not excluded that these are pre-Classical Armenian remnants. Apparently A. Meillet’s view according to which the disappearance of grammatical forms of dual number in languages, including Armenian, must beexplained by the progress of civilization, is admissible.
Keywords: Dual number, Old Armenian, Proto-Indo-European language, Armenian dialects